PEMELIHARAAN MENGGUNAKAN PLATFORM WICOPE PADA UNIT VOLVO FMX 440 DI PT. BUKIT MAKMUR MANDIRI UTAMA - Andre Amba Matarru; Ahmad Ridoh (Department of Mechanical Engineering, University of Udayana, 2022)
One of the supporting mining activities at PT. Bukit Makmur Mandiri Utama is the maintenance of the truck vehicle unit, where the truck functions as a mode of transportation to transport various kinds of materials and other materials including fuel. The unit operates continuously causing a decrease in the level of reliability and causes frequent breakdowns and high downtime in mining units, including the Volvo FMX 440 truck unit. To minimize breakdown and downtime, a good maintenance system is needed to prevent engine damage. Scheduled maintenance systems or predictive maintenance using the Wicope Platform can minimize breakdown conditions. In order to obtain a maintenance mechanism that can increase the service life of a unit and component, it can also have an effect on saving the company's expenses in carrying out the maintenance process.